Dr. Brian Shafa — Deep Plane Facelift — Beverly Hills - Shafa, Brian (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Brian Shafa, practicing in Beverly Hills, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003349; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; beverly hills